Propaganda techniques: A discourse analysis of Resalat and Etemad-E Melli editorials / Seyed Ali Javadi - Seyed Ali, Javadi (2017)
This research contributes to a better understanding of the discursive struggles phenomenon to create a meaning. The current study was carried out under the Social Constructionism, Post Modernism and Critical paradigms with the use of theoretical framework of Laclau and Mouffe’s (2001) discourse theory. Laclau and Mouffe (2014) suggested that the authenticity in a society is with its discursive and political processes which determine our thoughts and acts which eventually shape the society. In fact, the election campaigns are among competitive discourses (semantic challenges) towards organising a society in a specific way (politics) and are essentially not between the subjects, which are only performers in certain situations within the discourses. Since the mass media are one of the most important channels for discursive representations in the society, they are considered as a central emerging area of discursive struggles for consolidation of meanings. On this basis, the topic of this thesis has been developed, namely to make an appropriate decision on assigning power to a discourse (in discursive campaigns) which requires a transparent information and safe communication processes. This is a global need since the main obstacle is the ambiguity and distortion of information. The study has been carried out based on a qualitative research method namely critical discourse analysis. It focuses on the two principal discourses in Iran, namely the Iranian Islamic Principlism discourse (represented by Resalat newspaper) and the Iranian Reformism discourse (represented by Etemad-e Melli newspaper). The research has covered all editorials in the two above-mentioned newspapers, published from Saturday, 4thApril 2009 to Friday, 12th June 2009. Based on the interpretation of the results, it could be concluded that the discourses were struggling with each other over getting hegemony (relative consolidation of meaning). How these discourses were trying to dominate their own ways of understanding from the world and their definitions of local and global events over people’s minds and as a result their favourite social orders will be dominanted in the socity. In order to achieve this purpose, they must attribute their intended signifieds to the relevant floating signifiers to create meanings and images (discursive mechanism of representation).